2022
DOI: 10.3390/su14031488
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Hospital Safety Index for Analyzing Primary Healthcare Center (PHC) Disaster and Emergency Preparedness

Abstract: The World Health Organization (WHO) defines the primary healthcare center (PHC) as a whole-of-society approach to health that aims at ensuring the highest possible level of health and well-being and their equitable distribution by focusing on people’s needs as early as possible along the continuum from health promotion and disease prevention to treatment, rehabilitation, and palliative care, and as close as feasibly possible to people’s everyday environment. PHCs are expected to remain operational when disaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…It was used to assess the health care facilities' non-structural safety, which included water supply systems, locations of water tanks, water quality control, sanitation systems, heating, ventilation, HVAC, and/or hot water systems. In Greece, Iran and Indonesia, the HSI was also used to formulate recommendations to improve water supply safety ( 15 , 26 , 33 ), whereas in Serbia the usefulness of the HSI for safety assessment of a primary health care center was further evaluated ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was used to assess the health care facilities' non-structural safety, which included water supply systems, locations of water tanks, water quality control, sanitation systems, heating, ventilation, HVAC, and/or hot water systems. In Greece, Iran and Indonesia, the HSI was also used to formulate recommendations to improve water supply safety ( 15 , 26 , 33 ), whereas in Serbia the usefulness of the HSI for safety assessment of a primary health care center was further evaluated ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another example is evacuation plans that do exist but that are not mentioned in preparedness, making actual preparedness partly difficult to assess. Many case studies reported the need to specifically improve water supply preparation, but the assessment of hospital preparedness is often limited to its overall evaluation, e.g., using hospital safety index ( 15 , 26 , 33 ). Health care facilities with reported preparedness and response mechanisms are mostly among the larger ones described, raising the question if smaller facilities are really less prepared or simply less researched and less often rescued during emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Disaster Risk Reduction (DRR) community is increasingly considering hospital preparedness by developing new tools and frameworks, such as the CADRI tool. By doing so, this community is bringing a new perspective of hospital sustainability into hospital preparedness for disasters, and it is being given more and more consideration [ 36 , 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not well known worldwide and has only recently been used more frequently. Despite the recognized importance of strengthening disaster preparedness at all levels of the health system, literature supporting primary healthcare disaster preparedness is scant and lacks rigour [ 39 , 44 ]. There is no internationally recognized and validated method for evaluating the safety of PHC centres in case of disasters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation